Penatalaksanaan Fisioterapi Pada Kasus Low Back Pain Et Causa Spondilosis Lumbal Di Rumah Sakit PKU Muhammadiyah Surakarta - Fevharianti, Nabilla Aulia; , Dwi Kurniawati, SST.FT, M.Kes (2016)
Background: Lumbar spondylosis can be interpreted as a changed of the spinal joints with the increasing characteristic degeneration of the intervertebral disc followed by changed in bone and soft tissue, or it can mean excessive growth of bone (osteophytes), which are mainly located in the anterior aspect, lateral, and sometimes the posterior edge of the superior and inferior vertebrae centralis (corpus) in the case can be dealt with physiotherapy modalities. Physiotherapy in these cases can reduce pain, increase range of motion, increase muscle strength and improve functional ability using Infrared, Transcutaneus Electrical Nerve Stimulation (TENS) and William Flexion Exercise. Objective: To know the implementation of physiotherapy in reducing pain, increasing range of motion, increase muscle strength and improving functional ability in cases of low back pain due to lumbar spondylosis using Infrared modalities, Transcutaneus Electrical Nerve Stimulation and William Flexion Exercise. Results: After 6 times of treatment the obtained results is pain assessment for tenderness at T1: 3.6 into T6: 2.3, painful motion T1: 5.8 into T6: 4.6, the increase range of motion in lumbar flexion T1: 5 cm to T6: 6 cm, lateral flexion of the left T1: 9 cm into T6: 8 cm, the increase muscle strength in lumbar flexor T1: 3 into T6: 4, improvement in functional ability score results T1: 29 to T6: 24. Conclusion: Infrared, Transcutaneus Electrical Nerve Stimulation and William Flexion exercise can reduce pain, improve range of motion of lumbar, increase muscle strength and improve functional ability. Keywords: Low back pain et causa lumbar spondylosis, Infrared,Ttranscutaneous Electrical Nerve Stimulation (TENS) and William Flexion Exercise.